(untitled) (Research, Society and Development, 2020)
Caatinga, which is home to a rich floristic diversity with great potential for use, especially the woody component, which can be used as raw material in different industrial sectors generating income and moving the local economy. The present work aims to perform the macroscopic characterization of the wood of five native Caatinga species – Myracrodruonurundeuva, Anadenantheracolubrina, Sennatrachypus, Cedrelaodorata and Amburanacearensis. To carry out this research, 28 samples of each species were utilized. The macroscopic characterization of the woods was performed with the aid of a magnifying glass (10x). It was found that the axial parenchyma can be a character of strong relevance for the determination of the species. The macroscopic characteristics of the studied woods can be used with complementary information to identify and use options for the species evaluated.